(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
Based on the actual materials of exploration and exploitation of deposits of the marked industrial types the limiting errors of the average contents of metals at different stages of investigation are determined. The questions of correlation between the necessary degree of objects exploration and reserves of various categories are also considered. spatial time of desertification allocation, but also give forecast possibilities.